Evaluation the effect of image sharpening filter on diagnosis of external root resorption in apical portion induced by impacted tooth using cone beam computed tomography - Marzie Mazhari; Ali Habibikia; Ali Badfar; Mehdi Sabaghian; Arash Dabbaghi; Fattaneh Ghorbani Javadpour (Tehran University of Medical Sciences, 2022)
Background and Aims: By using the image processing capability in Cone-Beam Computed Tomography (CBCT), obtained information can be improved. The aim of the present study was to investigate the effect of sharpen image processing filter in determining the external resorption of the root apical region in single-rooted teeth due to the proximity of the impacted tooth using CBCT. Materials and Methods: In this laboratory study, the lateral surfaces of the apical region of the root of 40 healthy extracted teeth were artificially cut by bur and the teeth were randomly divided into four groups: control, low, moderate, and high resorption. After preparing CBCT of the teeth, the samples were then processed with and without an image sharpening processing filter and examined by two observers. The results of this study were analyzed by SPSS22 and Medcalc Statistical Software version 14. The significance level was considered P≤0.05 for all the statistical tests. Results: Specificity (100%) and sensitivity (66%>) were either complete or very high for both modes without and with the sharpen filter. The overall accuracy (0.83>) was high in both cases and no significant difference was observed between the two overall accuracies (P>0.05). Statistical analysis of both image observations by two observers showed that the overall sensitivity and accuracy in the medium and high resorption groups was much higher than the low resorption group, but the specificity in all groups was 100%. Conclusion: The results showed that the images with a sharpening filter did not increase the detection power compared to the unfiltered images. However, as no loss of accuracy was observed with this filter, it could be used as a processing filter.